Bridging the concepts of resilience, fragility and stabilisation. Issue 1 (2nd February 2015) - Manyena, Siambabala Bernard; Gordon, Stuart
Abstract : Purpose: – The fragile states and stabilisation concepts appear to resonate with the concept of community resilience. Yet, there is barely a framework that integrates the three concepts. The authors posit that despite the increasing interest in community resilience in fragile states, there is much less clarity of resilience, fragility and stabilisation connections. The paper aims to discuss these issues. Design/methodology/approach: – This paper is based on the literature review of the concepts of community resilience, fragility and stabilisation. Findings: – The findings restate that the state fragility results from the breakdown of the social contract between the state and its citizens. Whilst both resilience and stabilisation are desirable constructs in reducing fragility, they should be broadly underpinned by agency not only to enhance preventive, anticipatory, absorptive and adaptive actions but also lead to social transformative capacity where agency is embedded for communities to exercise some sort of power to foster change. Originality/value: – This paper has encourages debate on resilience, fragility and stabilisation connections by suggesting framework for "doing" resilience-informed stabilisation programmes in fragile states. The framework, which may not necessarily be approached in a linear fashion, has three major components: identifying existing resilience factors, enhancing and sustaining these and delivering resilient communities. However, there is need to test the utility of the framework in practice.